2020
DOI: 10.21203/rs.3.rs-18394/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ambulatory end-stage liver disease in Ghana; patient profile and utility of alpha fetoprotein and aspartate aminotransferase - platelet ratio index

Abstract: Background: End-stage liver disease (ESLD) is a major burden on public health, particularly in sub-Saharan Africa, where hepatitis B virus (HBV) is an important risk factor. We aimed to describe clinical characteristics of ESLD from cirrhosis or hepatocellular carcinoma (HCC) and the performance of aspartate aminotransferase (AST) - platelet ratio index (APRI) and alpha fetoprotein (AFP) in Ghana. Methods: We performed an observational cross-sectional study in outpatient hepatology clinics at three teaching h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 13 publications
2
8
1
Order By: Relevance
“…Another reason is the possibility that patients had insufficient test results for practitioners to arrive at a more specific diagnosis, as is common-place in low-resource settings. This may be related to the high cost of care associated with these conditions, which is often a barrier to definitive diagnosis and treatment [ 15 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reason is the possibility that patients had insufficient test results for practitioners to arrive at a more specific diagnosis, as is common-place in low-resource settings. This may be related to the high cost of care associated with these conditions, which is often a barrier to definitive diagnosis and treatment [ 15 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively lower burden of HBV-related ESLD in regions such as parts of Europe and North America are related to effective and stringent measures including injection blood safety, infection control strategies, antenatal screening and widespread acceptability of childhood vaccination [ 25 ]. Previous studies in Ghana have reported the high proportion of liver cancer and liver cirrhosis cases attributable to HBV infection [ 4 , 15 , 16 ], and this emphasizes the need for improved policies and strategies to reduce the HBV burden in Ghana. Although there is a national policy on viral hepatitis [ 26 , 27 ], the country has been unable to meet diagnosis and treatment targets for HBV and HCV infection, is yet to attain elimination goals, and has no published financing plan to achieve these aims.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was determined using Cochran's formula for sample size calculation. With an estimated prevalence of 12.5% for HBV in Ghana (12), a Z -score at 95% confidence level (1.96), and a level of significance of 0.05, the minimum sample size was calculated to be 166. Due to the high attrition rate for prospective studies, 334 participants were consecutively recruited after meeting the study criteria and giving informed consent.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…The most critical problem in the management of CHB in Africa including Ghana is the high cost of laboratory tests and drugs. One of the barriers identified in this country to HBV treatment is the high cost; however, this was based on qualitative studies [11,12]. Anecdotal evidence suggests that drugs for treatment may not be widely available, especially in district hospitals in Ghana and even if available may be too expensive for patients to buy.…”
Section: Introductionmentioning
confidence: 99%